Becoming notebook. The notebook as a body and the body as a notebook in the literary production of Leopoldo María Panero - Vega Manrique, Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper propose an inmersion into Leopoldo María Panero’s production from the device-notebook paradigm. Due to the characteristics of the material, we extend this idea to the body that writes towards an undifferentiation of the surfaces. What happens to what escapes from order, from structure, from formal delimitation, from meaning, from shared signifiers? What figures appear on these other surfaces? What forms of reading and approach do they produce?